(untitled) (World Bulletin of Public Health, 2024)
It is difficult to imagine modern medicine without high-tech equipment. It makes quick and accurate not only the diagnosis of most diseases, but also ensures the safe and low-traumatic performance of many manipulations. The downside is that doctors lose some skills, but the benefits from the development of technology are disproportionately greater. This article discusses the role of diagnostic equipment (ultrasound, CT) in the most important area - providing venous access necessary for the treatment of children with cancer